A study on health tourism industry: a case study among customer at spa in Bandar Hilir, Melaka / Aqilla Farihah Jumaat, Mohd Firdaus Abdul Rahim and Nur Amanina Halim - Jumaat, Aqilla Farihah; Abdul Rahim, Mohd Firdaus; Halim, Nur Amanina (2014)
This research attempts to study customer’s satisfaction towards spas in Bandar Hilir, Melaka. This report is the outcome of a field research, which aimed to determine the quality of services offered by spas in Bandar Hilir, Melaka. This paper aims to discover what customers feel and think of the quality of service as can be found in the spas in Bandar Hilir, Melaka.